Bradykinin-mediated angioedema: factors associated with admission to an intensive care unit, a multicenter study. (June 2016) - Javaud, Nicolas; Floccard, Bernard; Gontier, Florian; Lapostolle, Frédéric; Boccon-Gibod, Isabelle; Martin, Ludovic; Amarger, Stéphanie; Boumedienne, Abdalia; Boubaya, Marouane; Asfar, Pierre; Coppere, Brigitte; Ollivier, Yann; et al.
Abstract : Objective: Bradykinin-mediated angioedema is characterized by transient attacks of localized edema of subcutaneous or submucosal tissues and can be life-threatening when involving the upper airways. The aim of this study was to determine the features of acute attacks that might be associated with admission to an ICU. Patients and methods: We carried out a retrospective, multicenter, observational study in consecutive patients attending one of six reference centers in France for acute bradykinin-mediated angioedema attacks. Patients had been hospitalized for an acute episode at least once previously. Acute attacks requiring ICU admission were compared with acute attacks that had not required ICU admission. Results: Overall, 118 acute attacks in 31 patients were analyzed (10 patients with hereditary angioedema, 19 patients with angiotensin-converting enzyme inhibitor-induced angioedema, and two patients with acquired C1-inhibitor deficiency angioedema). In multivariate analysis, upper airway involvement, corticosteroid, and C1-inhibitor concentrate administration were associated with ICU admission. Seven episodes (18%) needed airway protection. The evolution was favorable in 38 of 39 attacks warranting ICU admission: patients were able to get out of the service (mean ICU stay 4±5 days). One death was observed by asphyxiation because of laryngeal swelling. Conclusion: Upper airway involvement is an independent risk factor for ICU admission. Corticosteroid use, which is an ineffective treatment, and C1-inhibitor concentrate use are factors for ICU admission. The presence of upper airway involvement should be a warning signal that the attack may be severe.